2017
DOI: 10.1016/j.bbrc.2017.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-Terminal Hydrolase L1 regulates myoblast proliferation and differentiation

Abstract: Skeletal muscles are dynamic tissues that possess regenerative abilities, which require multiple processes and regulatory factors. Ubiquitin C-Terminal Hydrolase L1 (UCHL1), which is primarily expressed in neuronal tissues, was upregulated in skeletal muscles in disease conditions but its functional role in skeletal muscles is unknown. Using mouse myoblast cells C2C12 as an in vitro model, this study reported that UCHL1 elicits different regulation in myoblast cell proliferation and differentiation. We first o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Originally discovered as a neuronal protein, UCHL1 has not been recognized to also express in skeletal muscle until recently [ 13 , 14 ], and its functional roles in the muscle remain unclear. We recently reported that UCHL1 has an inhibitory effect on myoblast C2C12 differentiation [ 15 ]. The results of the present study reveal for the first time that UCHL1 is present in oxidative skeletal muscles and is essential for muscle oxidative activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Originally discovered as a neuronal protein, UCHL1 has not been recognized to also express in skeletal muscle until recently [ 13 , 14 ], and its functional roles in the muscle remain unclear. We recently reported that UCHL1 has an inhibitory effect on myoblast C2C12 differentiation [ 15 ]. The results of the present study reveal for the first time that UCHL1 is present in oxidative skeletal muscles and is essential for muscle oxidative activity.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was performed as described previously [ 20 , 23 , 24 ]. Briefly, samples of 15–30 μg of total proteins were subject to electrophoresis in 9–15% gradient gels at 100 V for 2 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found that UCHL1 plays important roles in cell differentiation. For example, Gao H et al demonstrated that UCHL1 played a role in myogenesis by inhibiting differentiation [ 36 ], while Sakura et al found that UCHL1 could regulate the morphology of neural progenitor cells and modulate their differentiation thereby enhancing neurogenesis in the embryonic brain [ 25 ]. In this study, we found that UCHL1 expression was significantly higher in GNB/GN and well-differentiated NB than poorly differentiated NB, and UCHL1 expression was positively correlated with the known neural differentiation markers.…”
Section: Discussionmentioning
confidence: 99%